2020
DOI: 10.1002/psp.2324
|View full text |Cite
|
Sign up to set email alerts
|

Job changing and internal mobility: Insights into the “declining duo” from Canadian administrative data

Abstract: Considerable research focuses on why internal migration rates are declining across most of the Western world. Several studies also look at why people are less likely to change jobs than they were in the past. In this paper, we look at the prospect of declining economic returns as an explanation for the joint decline in both phenomena in Canada. We use the Canadian Employer‐Employee Dynamics Database, a linked job–individual–family–firm data set, to look at the 5‐year income trajectories for Canadian workers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Our main measure of individual income is the hourly wage from paid employment, which we compute for all workers who are employed as wage workers. 2 We find that when pooling individuals across all core countries, hours per worker fall with wages just as they do in the aggregate: the slope of log hours on log wages is −0.10, compared to a slope of log hours on log GDP per hour of −0.12. When regressing log hours on both log wages and log country GDP per hour together, the slope on log wages falls only modestly, while the coefficient on GDP per hour becomes substantially smaller in absolute terms.…”
mentioning
confidence: 68%
“…Our main measure of individual income is the hourly wage from paid employment, which we compute for all workers who are employed as wage workers. 2 We find that when pooling individuals across all core countries, hours per worker fall with wages just as they do in the aggregate: the slope of log hours on log wages is −0.10, compared to a slope of log hours on log GDP per hour of −0.12. When regressing log hours on both log wages and log country GDP per hour together, the slope on log wages falls only modestly, while the coefficient on GDP per hour becomes substantially smaller in absolute terms.…”
mentioning
confidence: 68%
“…Evidence from North America is, however, contradictory. Haan and Cardoso (2020) and Kaplan and Schulhofer‐Wohl (2017) found that a reduction in the economic returns to migration has reduced internal migration, whereas Li et al (2020) argued that the disparities do not play a significant role in inter‐state migration in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This decline has often been explained in relation to Zelinsky (1971)'s mobility transition hypothesis, which predicted that internal migration would be partially substituted by technological progress that facilitates other forms of mobility such as long‐distance commuting, particularly in advanced societies. Other explanations include population ageing (Cooke, 2011; Karahan & Rhee, 2014) and a reduction of economic opportunities across regions (Haan & Cardoso, 2020; Kaplan & Schulhofer‐Wohl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Immobility is a recognised term in the German-speaking community in the context of migration and climate change. Here it is considered one outcome of livelihood decision-making (see Sakdapolrak et al, 2016;Hillmann and Ziegelmayer, 2016). The topic of immobilities further emerges in the broad discourse on multi-locality.…”
Section: Overview and Status Quo Of Immobility Researchmentioning
confidence: 99%
“…In recent years, it was however discovered to be heavily dependent on economic factors, e.g. on fewer economic returns when switching jobs and/or on geographical locations (Haan and Cardoso, 2020).…”
Section: Reasons For and Factors Influencing (Increasing) Immobility And Implications Of Immobilitiesmentioning
confidence: 99%